P248 THE SCORE TELEHFCOVID19, ONE MONTH FOLLOW UP : A TELEHEALTH APPROACH TO MANAGE ELDERLY PATIENTS WITH CHRONIC HEART FAILURE DURING COVID–19 PANDEMIC. (18th May 2022) - Salucci, C; Girardi, E; Orso, F; Herbst, A; Migliorini, M; Ghiara, C; Virciglio, S; Camartini, V; Tognelli, S; Fortini, G; Di Bari, M; Baldasseroni, S; et al.
Abstract: Background: Due to the total lockdown during COVID–19 pandemic, clinicians were forced to organize telephone visits or tele–monitoring. We developed a standardized multiparametric questionnaire, suitable for telephone administration to older heart failure (HF) patients and/or their caregivers. Purpose: To compare clinical characteristics of the three groups (green, yellow, red) of patients classified by baseline TeleHFCovid19–Score and evaluate its ability to predict one–month in elderly patients with chronic HF. Methods: The TeleHFCovid–19 score was obtained from a multiparametric questionnaire administered, from April 2020, during televisits to patients (or caregivers), which were divided in progressively increasing risk groups: green (0–3), yellow (4–8) and red (≥9). The primary study outcome was a composite of death from cardiovascular causes and/or hospitalization for HF, which individually were secondary outcomes. Results: We enrolled 146 patients. Mean age was 81±9 years, females were 40%. In all the study population there was a high prevalence of self–reported adherence to guidelines–recommended drug treatments and behavioural measures, as well as a broad intake of diuretic therapy. Patients in green group had lower use of high dose loop diuretic (p < 0.001) or thiazide–like diuretic and had reported less frequently dyspnoea at rest or for basic activities, new/worsening extremities oedema or weight increase (all p < 0.001). Through scheduled phone contacts we were able to improve the overall clinical status of our patients even over a short (1 month) follow–up.The primary composite outcome of CV death and/or HF hospitalisation occurred in 8.2%, with a significantly lower prevalence in the green than in the yellow and red groups, and when analysing separately, we found that death for CV causes occurred more frequently in the red group than in the other two, while HF hospitalisations were significantly less frequent in the green group than in the red or yellow. ROC analysis confirmed the high sensibility and specificity of our score (AUC=0.883, 95% CI 0.806–0.959) with a score <4.5 (very close to green group cut–off) that identified lower–risk subjects (p < 0.001). Conclusions: The TeleHFCovid19–Score score was able to correctly recognize a low risk, green group. Therefore, the score could be used to identify low risk patients which could be followed remotely, reserving a tighter on–site clinical follow–up to higher events risk patients.